Teachers’ organizational citizenship behavior: the Malaysia scenario - Ismail, Suriani; Hassan, Roshafiza (Human Resource Management Academic Research Society, 2024)
Increased economic competition, both within and between nations, results from globalization. Economic competitiveness is thought to promote the development of human capital. According to earlier research, an organization will only succeed if its workers put in much effort each day to complete their tasks and support their efforts to remain productive and competitive. Extra-role behavior, or organizational citizenship behavior (OCB), is the term used to describe this circumstance. Still, the research on OCB among Malaysian teachers is relatively new. Hence, this study examines the scenario of teachers’ OCB in Malaysia. A total of 824 secondary school teachers in Malaysia participated in this study. The findings revealed that the level of teachers' OCB in Malaysia is moderate. Additionally, this study showed that the OCB level by dimensions. The study also looked at the response distribution to illustrate the OCB scenario among teachers. The current study made the case that additional empirical research on OCB in educational settings is necessary to improve OCB among teachers, enhancing their effectiveness and the success of their schools.